A simple procedure to identify children with B‐lineage acute lymphoblastic leukemia who can be successfully treated with low or moderate intensity: Sequential versus single‐point minimal residual disease measurement. Issue 6 (28th March 2023) - Popov, Alexander; Henze, Guenter; Roumiantseva, Julia; Budanov, Oleg; Belevtsev, Mikhail; Verzhbitskaya, Tatiana; Boyakova, Elena; Movchan, Liudmila; Tsaur, Grigory; Fadeeva, Maria; Lagoyko, Svetlana; Zharikova, Liudmila; et al.
Abstract: Sequential monitoring of minimal residual disease (MRD) by molecular techniques or multicolor flow cytometry (MFC) has emerged over the past two decades as the primary tool to optimize treatment in pediatric B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL). The aim of our study was to compare the prognostic power of repeated MFC–MRD measurement with single‐point MRD assessment in children with BCP‐ALL treated with the reduced‐intensity protocol ALL‐MB 2008. Data from consecutive MFC–MRD at day 15 and day 36 (end of induction, EOI) were available for 507 children with Philadelphia‐negative BCP‐ALL. They were stratified into standard risk (SR, n = 265), intermediate risk (ImR, n = 211), and high risk (HR, n = 31) according to the initial clinical characteristics defined in the ALL‐MB 2008 protocol. Quantitative (relative to quantitative thresholds) and kinetic (logarithmic reduction) assessments of MFC–MRD at both time points effectively separated patients into three groups with different risk of recurrence. On the other hand, starting with low (for the SR group) and moderate (for the ImR group) induction therapy, a single MFC–MRD measurement at EOI proved sufficient to unequivocally identify patients in whom this therapy is highly effective and distinguish them from those who cannot be successfully treated with such therapy. Therefore, initiating treatment with low or moderate treatment from the start, together with careful consideration of initial clinical risk factors and just one EOI–MFC–MRD measurement is simple, inexpensive, and entirely sufficient for treatment optimization. Furthermore, for a large proportion of patients, this approach allows better adjustment, in particular also reduction of therapy intensity than sequential MRD measurements.